2017
DOI: 10.2989/16085906.2017.1285795
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of agency and constraint for HIV-positive patients and healthcare workers to support long-term engagement with antiretroviral therapy care in Khayelitsha, South Africa

Abstract: In the context of the optimism around antiretroviral therapy (ART) as prevention of HIV/AIDS, addressing the barriers to long-term ART adherence is critical. This is particularly important given the tendency to individualise or use a blame discourse when exploring why HIV-infected patients “fail” to adequately adhere to ART, and not sufficiently exploring contextual reasons for poor adherence that may require varying solutions. This study took place at three clinics and one hospital in Khayelitsha, South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…Other researchers have also shown that PLHIV often blame themselves for dis-engaging from care, and that this sense of guilt and fault need to be carefully navigated by health care workers as they move forward in their treatment journeys (Layer et al, 2014). In addition, the precarity of the social transformations that accompany regimen change that we observed echo the findings in Russell and Seeley's research in Uganda among individuals who initiated first-line ART following HIV-related illnesses and recall the complexity of achieving sustained engagement with HIV care and treatment in the context of pervasive stigma and challenging social circumstances Skovdal et al, 2017;Stern, Colvin, Schutz, Burton, & Meintjes, 2017;Wamoyi et al, 2017). Other researchers have also noted apparent contradictions or paradoxes in the experiences of patients who have very long treatment histories, whereby optimism and hope often co-exist alongside new challenges that arise from sustained treatment-taking, and which may risk undermining treatment-taking (Nixon et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…Other researchers have also shown that PLHIV often blame themselves for dis-engaging from care, and that this sense of guilt and fault need to be carefully navigated by health care workers as they move forward in their treatment journeys (Layer et al, 2014). In addition, the precarity of the social transformations that accompany regimen change that we observed echo the findings in Russell and Seeley's research in Uganda among individuals who initiated first-line ART following HIV-related illnesses and recall the complexity of achieving sustained engagement with HIV care and treatment in the context of pervasive stigma and challenging social circumstances Skovdal et al, 2017;Stern, Colvin, Schutz, Burton, & Meintjes, 2017;Wamoyi et al, 2017). Other researchers have also noted apparent contradictions or paradoxes in the experiences of patients who have very long treatment histories, whereby optimism and hope often co-exist alongside new challenges that arise from sustained treatment-taking, and which may risk undermining treatment-taking (Nixon et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…This is corroborated by surveys of HIV-associated morbidity in inpatient wards, where tuberculosis has been a major contributor to clinical presentation [ 19 ]. There is growing evidence that the successes of HIV treatment access are resulting in a sizeable population of individuals on ART who are vulnerable to rapid deterioration as they cycle in and out of care, as many do, owing to both service and personal challenges [ 12 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second theory hypothesizes that health services have been designed for women, and men have been systematically left out [ 10 ]. These theories are also influenced by contextual barriers including poverty, stigma and distrustful and difficult relationships with HCWs [ 33 ]. The findings of this study build on these two theories and provide an additional perspective; that outdated beliefs about HIV care and treatment deter men from engaging in HIV testing and treatment.…”
Section: Discussionmentioning
confidence: 99%